Double-O-Tube Shield Tunneling-Induced Soil Displacement Considering Burial Depth and Convergence Mode: Transparent Soil Experiment and DEM Simulation - Zeng, Bin; Zhu, Yucong; Ye, Siqiao; Zheng, Yong; He, Lei; Ma, Rui (Frontiers in Earth Science, 2022)
Double-O-tube shield tunneling technology has gained extensive attention due to saving space and the high cost-effectiveness of the underground construction method. Estimating and predicting DOT shield tunneling-induced soil displacements is essential to prevent damage to nearby aboveground and underground structures in densely populated urban areas. This paper develops a device for modeling DOT shield tunneling based on transparent soil technology and image processing technique and investigates soil displacement during the construction process of the DOT shield tunnel, which is considered in the uniform convergence mode (UCM) of soil loss. Meanwhile, the soil displacement under the non-uniform convergence mode (NCM) is analyzed contrastively using a two-dimension particle flow code (PFC2D). The results show that horizontal displacements increase gradually when the shield tail passes the monitoring face, while settlements increase rapidly. The maximum horizontal displacement of the surface and the maximum surface settlement under NCM are slightly larger than that under UCM. A trapezoid-shaped failure pattern of soil is experienced at three tunnel depths. The maximum soil displacement under NCM is 1.93, 2.10 and 2.05 times, respectively, as much as that under UCM, corresponding to H/D (the ratio of the tunnel depth to the tunnel diameter) =1.0, 1.5 and 2.0. The soil arch effect above DOT tunnels arises as the DOT tunnel depth increases. Moreover, the experimental and numerical results are adopted to assess the validity of the proposed model, which indicates that the proposed model is close to the test results of the disturbance zone on DOT tunnels.